All together now: a multi-language and multi-system mobile application to make live performing arts accesible - Estella Oncins; Oscar Lopes; Pilar Orero; Javier Serrano; Jordi Carrabina (JoSTrans: The Journal of Specialised Translation)
Stage performances are usually live performances. These days, theatre or opera may be staged anywhere from the traditional seating arrangement to a popular open air representation where actors and audience move in a dynamic open mise en scène. In some theatre houses, accessibility to the audio (subtitles) and visual elements of the performances (audio description) has been arranged through the installation of screens on the back of seats, or through the projection of surtitles on a large screen usually located above the stage. In some cases, both practices coexist to show in written form what is being spoken or sung, translated into the vernacular, and audio described to provide a user-friendly representation. Surtitles, subtitles, audio description, audio subtitling and some other accessible services are being increasingly required by European Directives relating to media content. Yet many barriers still make accessibility an almost utopian ideal. Intelligent mobile phones and the widespread availability of applications may be the way to solve access to live performances, and this is the subject of this paper. The article will first present the many challenges that exist in a live production where synchronous accessibility should be provided. It then presents the system – Universal Access System (UAS) — which has been developed to deliver most accessibility services for live performances via a mobile application.